2015
DOI: 10.1016/j.cognition.2014.10.006
|View full text |Cite
|
Sign up to set email alerts
|

The tree to the left, the forest to the right: Political attitude and perceptual bias

Abstract: A prominent model suggests that individuals to the right of the political spectrum are more cognitively rigid and less tolerant of ambiguity than individuals to the left. On the basis of this model, we predicted that a psychological mechanism linked to the resolution of visual ambiguity--perceptual bias--would be linked to political attitude. Perceptual bias causes western individuals to favour a global interpretation when scrutinizing ambiguous hierarchical displays (e.g., alignment of trees) that can be perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…Prior to this work, numerous studies have reported a global bias in normally developing adults in both Western and Asian cultures (e.g., Caparos et al, 2015;De Lillo et al, 2005;Lachmann et al, 2014;McKone et al, 2010) and just a handful of studies have reported a local bias in one population of normally developing adults (Bremner et al, 2016;Caparos et al, 2012;Davidoff et al, 2008;de Fockert et al, 2007). The latter population is remote, uneducated and illiterate, namely, the Himba of Northern Namibia (Southern Africa).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Prior to this work, numerous studies have reported a global bias in normally developing adults in both Western and Asian cultures (e.g., Caparos et al, 2015;De Lillo et al, 2005;Lachmann et al, 2014;McKone et al, 2010) and just a handful of studies have reported a local bias in one population of normally developing adults (Bremner et al, 2016;Caparos et al, 2012;Davidoff et al, 2008;de Fockert et al, 2007). The latter population is remote, uneducated and illiterate, namely, the Himba of Northern Namibia (Southern Africa).…”
Section: Discussionmentioning
confidence: 98%
“…Inspired by Navon's work in 1977, the general view has persisted until the present that there exists a universal global bias (e.g., De Lillo, Spinozzi, Truppa, & Naylor, 2005;Lachmann, Schmitt, Braet, & van Leeuwen, 2014;Poirel, Mellet, Houdé, & Pineau, 2008), with an abundant number of studies reporting a global bias in normally developing Western and Asian participants (e.g., Caparos, Fortier-St-Pierre, Gosselin, Blanchette, & Brisson, 2015;Lachmann et al, 2014;Mahoney, Brunyé, Giles, Lieberman, & Taylor, 2011;McKone, Davies, Fernando, Aalders, Leung, Wickramariyaratne, & Platow, 2010;Poirel et al, 2008). Recent data have however shown that the Himba of Northern Namibia (Southern Africa), a normally developing non-western population living a traditional lifestyle in remote rural settlements, show a strong local perceptual bias (Bremner, Doherty, Caparos, De Fockert, Linnell, & Davidoff, 2016;Caparos, Ahmed, Bremner, De Fockert, Linnell, & Davidoff, 2012;Davidoff, Fonteneau, & Fagot, 2008;De Fockert, Davidoff, Fagot, Parron, & Goldstein, 2007).…”
Section: The Local Perceptual Bias Of a Non-remote And Educated Populmentioning
confidence: 99%
“…While many diverse issues are often clustered into party politics or conservative versus liberal orientations, including views on economic policies, religion, inequality, environmental protection, and civil rights, nationalism tends to focus primarily on perceptions of national superiority and idealization of the nation and its dominance or history (2)(3)(4). Thus, it is important to explore how the findings from political psychology-which have identified differences between conservatives and liberals in their personalities (16,17), need for order and structure (13,18,19), cognitive control and inhibition (20), and physiological reactivity (15,21,22)-translate into the study of nationalistic ideology.…”
mentioning
confidence: 99%
“…If dartboards truly look larger after a subject hits them with darts (Cañal-Bruland et al, 2010), then a recently hit dartboard presented next to both (a) an un-hit dartboard of the same size, and (b) an unhit dartboard that is objectively larger, should appear to resemble the larger dartboard object in size, such that the equally sized un-hit dartboard should stand out as different in size. If objects truly look closer when they are desired (Balcetis & Dunning, 2010), then a desired object presented near (a) a neutral object of the same distance, and (b) a neutral object that is objectively closer, should resemble the closer object in distance, and the equally distant neutral object should stand out as different in distance (so too with other reported spatial distortions; Caparos et al, 2015;Fini, Brass, & Committeri, 2015;Harber et al, 2011). Any of these findings would strengthen the case for those alleged top-down effects of cognition on perception (though there may of course be other pitfalls lurking in the background; Firestone, 2013a;Firestone & Scholl, 2016).…”
Section: Generally Applicablementioning
confidence: 99%